O Bullying como discurso civilizador: uma análise sociológica do programa “conte até dez nas escolas”. - Silva, Raquel Angelino da (Universidade Federal do Tocantins, 2019)
The present work has as an analysis the aspects that involve the ambiguities of the term bullying in the process of concealment of relations of power in the personal relations and prevailing conflicts in several fields. We have as object of material analysis of the program "Count up to ten in schools". We observe that actions like this exert a control over subjectivities, as they ignore important sociocultural aspects of the life trajectories on which they affect. We seek new reflections about the bullying phenomenon with the purpose of promoting a deepening of the discussion around the term, since a trend is pointed out in maintaining the definition of bullying as being only a behavior linked to physical and psychological aggression and that it has several forms of manifestation, to the detriment of an acceptance of the relations of power that give life